2015
DOI: 10.1186/s12906-015-0569-8
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of complementary and alternative medicine (CAM) among children from a German birth cohort (GINIplus): patterns, costs, and trends of use

Abstract: BackgroundThe use of complementary and alternative medicine (CAM) is widespread among children in Germany and other European countries. Only a few studies are available on trends in pediatric CAM use over time. The study’s objective was to present updated results for prevalence, predictors, and costs of CAM use among German children and a comparison with findings from a previous follow-up of the same birth cohort.MethodsData were collected for 3013 children on their utilization of medicinal products (during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
2
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 16 publications
3
20
2
4
Order By: Relevance
“…Last but not least, strength of agreement between actual and predicted use of homeopathy was rather slight [38]. Despite these limitations, the current study expands previous findings on homeopathy use by various patient groups [18,19,20,21,22,23,24]. …”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Last but not least, strength of agreement between actual and predicted use of homeopathy was rather slight [38]. Despite these limitations, the current study expands previous findings on homeopathy use by various patient groups [18,19,20,21,22,23,24]. …”
Section: Discussionsupporting
confidence: 70%
“…Previous research has shown mixed results with regards to gender and homeopathy use. Findings from research targeting the general population support the view that women are more likely to use homeopathy [2,18,19]. However, research focusing on specific subgroups of the population, such as older adults [1] or cancer patients [3], reported no difference in homeopathy use based on gender.…”
Section: Discussionmentioning
confidence: 74%
“…Herbal drug use and consultation with CAM providers were positively associated with higher maternal education. Homeopathy was used most by girls and by participants residing in Munich, confirming the results from a previously published study analyzing only the GINIplus cohort [19]. …”
Section: Resultssupporting
confidence: 79%
“…The classification and the exact definition of the various modalities have been described in detail previously [19]. For the present study, the following medicinal CAM modalities were considered:…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that Chinese medicine practices including acupuncture, homeopathy, and Ayurvedic medicine are used for skin diseases in addition to herbal treatments (17). Homeopathy is especially widespread in some countries (6,(28)(29)(30)(31). Factors such as a lack of information and additional costs may have influenced why these methods were not used in our study.…”
Section: Discussionmentioning
confidence: 99%